2010
DOI: 10.1074/jbc.m110.180380
|View full text |Cite
|
Sign up to set email alerts
|

ARFGAP2 and ARFGAP3 Are Essential for COPI Coat Assembly on the Golgi Membrane of Living Cells

Abstract: Coat protein complex I (COPI) vesicles play a central role in the recycling of proteins in the early secretory pathway and transport of proteins within the Golgi stack. Vesicle formation is initiated by the exchange of GDP for GTP on ARF1 (ADP-ribosylation factor 1), which, in turn, recruits the coat protein coatomer to the membrane for selection of cargo and membrane deformation. ARFGAP1 (ARF1 GTPase-activating protein 1) regulates the dynamic cycling of ARF1 on the membrane that results in both cargo concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 61 publications
0
29
1
Order By: Relevance
“…These results suggest that normal AGD8 and AGD9 levels are crucial for the maintenance of the Golgi morphology. A previous study in animal cells demonstrated that knockdown of both ArfGAP2 and ArfGAP3 in animal cells caused similar alterations in Golgi morphology (Kartberg et al, 2010). Thus, it is possible that AGD8 and AGD9 are functional orthologs of the Glo3p-type ArfGAPs in animal cells, ArfGAP2/ArfGAP3.…”
Section: Rna Interference Transgenic Plants Expressing Lowmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that normal AGD8 and AGD9 levels are crucial for the maintenance of the Golgi morphology. A previous study in animal cells demonstrated that knockdown of both ArfGAP2 and ArfGAP3 in animal cells caused similar alterations in Golgi morphology (Kartberg et al, 2010). Thus, it is possible that AGD8 and AGD9 are functional orthologs of the Glo3p-type ArfGAPs in animal cells, ArfGAP2/ArfGAP3.…”
Section: Rna Interference Transgenic Plants Expressing Lowmentioning
confidence: 99%
“…If AGD8/AGD9 are Arabidopsis orthologs of Glo3p-type ArfGAPs, they are likely to be involved in a COPI-related process (i.e. in retrograde Golgi-toendoplasmic reticulum trafficking), as observed for Glo3p ArfGAPs (Frigerio et al, 2007;Kliouchnikov et al, 2009;Kartberg et al, 2010). However, it is technically very difficult to monitor retrograde trafficking in plant cells.…”
Section: Rna Interference Transgenic Plants Expressing Lowmentioning
confidence: 99%
“…Future studies will determine if the interaction of ArfGAP1 with Arf1 and cargo affects vesicle formation and whether other ArfGAPs, such as ArfGAP2 and 3 and AGAPs, that bind to coat proteins and cargo 12,15,[69][70][71] function by a mechanism analogous to ArfGAP1.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…The function of ArfGAP1, 2 and 3 is, at least in part, related to interaction with the substrate protein Arf1•GTP, vesicle coat protein and the cargo proteins that are being transported. [8][9][10][11][12][13][14][15] The molecular basis for retrograde traffic between the Golgi cisternae or from the Golgi apparatus to the ER has been extensively studied. 2,[4][5][6][7]16 In these pathways, cargo is transferred from trans-side cisternae to the more cis-side, or from the Golgi apparatus to the endoplasmic reticulum (ER).…”
Section: Introductionmentioning
confidence: 99%
“…ArfGAP2/3 followed the dynamics of membrane association of coatomer more closely than does ArfGAP1. Furthermore, ArfGAP2/3 knock down caused unstacking of the Golgi and cisternal shortening, similar to conditions in which vesicle uncoating was blocked (Kartberg et al 2010). Taken together, ArfGAP1, independent of coatomer, is likely to drive the cycle of activation and inactivation of Arf1 explained above, whereas the coatomer-dependent ArfGAPs2/3 are candidate-uncoating, GTPase-activating proteins.…”
Section: Uncoatingmentioning
confidence: 73%